SEABATHER'S ERUPTION: A CLINICAL and EPIDEMIOLOGICAL STUDY of 38 CASES IN SANTA CATARINA STATE, BRAZIL - Rossetto, Andre Luiz; Dellatorre, Gerson; da Silveira, Fabio Lang; Haddad Júnior, Vidal [UNESP] (Inst Medicina Tropical São Paulo, 2009)
Seabather's eruption (SBE) is an intensely itchy, papule-erythematous dermatitis that occurs predominantly in regions of the body covered by bathing costumes, after exposure to marine water. The planulae larvae of Linuche unguiculata scyphomedusae (thimble jellyfish) are the etiologic agent of the dermatitis, which is frequent in waters of Caribbean, Gulf of Mexico and Florida. The authors report 38 cases of SBE in the State of Santa Catarina (Southern region of Brazil), with emphasis on their clinical and epidemiological aspects, such as profile of victim, topography of the papules and conditions predisposing to the accident.
Keywords: Dermatitis; Linuche unguiculata; Cnidaria; Venomous marine animals, Brazil; Seabather's eruption